Estrés, Sobrecarga Y Ansiedad En Cuidadoras Primarias De Niños Que Padecen Leucemia En Hidalgo - Ríos, Karla Salinas; Martínez, Rodolfo de Jesús Acevedo; Arreola, Arturo Del Castillo; Saldaña, Rebeca María Elena Guzmán; Sánchez, José Esael Pineda (European Scientific Journal, ESJ, 2017)
Leukemia is the type of cancer that occurs more in children and teenagers. The chronic-degenerative nature of the disease makes that the minors need someone responsible for their care known as informal primary caregiver. Generally, the primary caregiver role, who attends all the patient needs, it’s acquired by the father or mother of the minor. The demands of that labor can bring negative physiological and psychosocial consequences. Objective: to determine the relationship and the difference by sex and disease phase of the minor in the levels of stress, burden and anxiety of primary caregivers of boys and girls with leukemia in Hidalgo. Method: through a non-probability sampling of volunteers subjects were selected N = 50 female primary caregivers. To measure the variables they were used the following instruments: Perceived Stress Scale, Zarit Caregiver Burden Scale and Beck Anxiety Inventory. Results: showed positive and statistically significant correlations between anxiety-burden and stress-anxiety. It also found that the caregivers of boys have higher levels of anxiety than caregivers of girls and caregivers of patients in active phase of the disease have higher burden compared with caregivers of patients in remission phase. Conclusion: there are some high levels of stress, burden and anxiety in caregivers. There exists correlation between anxiety-stress and burdenanxiety. The caregivers of boys have more anxiety. The caregivers of children in active phase of the disease present more burden.